Enhancing Discourse Markers Awareness among Iranian EFL Learners: A Product - Process Based View - Mohammad Shabani; Sana Goljani (Teaching English Language, 2015)
While several researchers have studied discourse markers to determine their roles in language skills, still research needs to address these devices in relation to second language learners writing proficiency Hence, the present study had two main goals: identifying the usage of discourse markers used in Iranian writing compositions without instruction, and describing how treatment of discourse markers functions in learners’ writing.. Participants in this study were 60 upper-intermediate and intermediate learners studying English as the second language at Safir, Qazvin branch. Descriptive composition writing was assigned to students to write on the topics, selected by the researchers and based on Fraser's (1990, 1999) taxonomy of discourse markers. The results indicate that within the explorative section, with the proficiency level rising, the frequency and the type of the discourse markers used subconsciously without the treatment rise. At the same time, the treatment and discourse marker awareness among the learners can be of significant value in both the quality and quantity of discourse markers. Of course, the type of the treatment must be adjusted to the proficiency level of the learners. This is in keeping with the previous research that reported a positive impact of instruction of DMs on success in language writing (Feng, 2010).